Examination of seasonal changes of some physical and technical parameters according to the positions of professional league players - Kayantasand, I.; Söyler, M. (International Journal of Applied Exercise Physiology, 2020)
The aim of this study is to determine whether there are differences between 25 footballers playing in different positions in terms of selected physical and physiological features. 25 male professional football players with different positions [goalkeeper (n = 3), defense (n = 9), midfield (n = 10), striker (n = 3)] voluntarily participated in the study. Football players' ages, body weights, height, flexibility values, vertical jump values, 10 m reactionspeed, aerobic capacities (VO2max KAH) were determined. In order to provide information about the football players participating in the study, the frequency distributions, the averages, standard deviations, and the smallest and greatest values of the footballers according to their positions were calculated. Shapiro-Wilk test was used to determine whether the data showed normal distribution and as a result, "Single Way Variance Analysis (Anova)" was used to determine the difference between the groups since the data showed normal distribution. In cases where the difference occurred between the groups as a result of Anova, Tukey test was applied to determine which group the difference originated from. Paired Samples Test was used to examine the changes in the groups. For all statistical methods, the level of error (a) is accepted as 0.05. SPSS 20.0 package program was used in the statistical analysis of the data. According to Anova results; while there is a significant difference between positions in terms of height, vertical jump from selected physical and physiological features, there is no difference in remaining features. As a result, it is considered that the differences in the physical parameter characteristics of the players in different positions havedisappeared since the level of development and modernization of modern football and the running distances of football players in the match have become closer in today's football world.